Aggregation approaches to decentralized planning structures - Jörnsten, Kurt O.; Leisten, Rainer (Design models for hierarchical organizations, 1995)
Decomposition methods have been intensively studied both as techniques for solving large-scale models as well as a means for analysing different control mechanisms in quantitative approaches for decentralized planning structures. The reason for this latter application lies in the straight forward interpretation of most classical decomposition methods in terms of information flow between different levels in a decentralized organization. The development of aggregation approaches for the solution of large-scale models has not followed the same pattern. In this area, the emphasis has been on the algorithmic development and the efficiency of the aggregation methods as solution techniques. The interpretation of aggregation and disaggregation techniques as models for analysing control mechanisms in decentralized planning structures are sparse although there are some exceptions [1,2]. In this chapter, we compare different types of aggregation approaches with standard decomposition approaches focusing on their different formulations and on the informational requirements in different organizational structures, such as the functional or the multidivisional structure. We exemplify the different approaches by means of a small example and extend it partly to a well-known example for multidivisional and functional organization given by Burton/Obel [3].